Perancangan Perangkat Elektronik Media Pembelajaran Iqra dalam Kode Braille - Hidayat, Hidayat; Nugraha, Aditya (Jurnal Sistem Komputer, 2016)
Iqra Learning is the first step in studying al-Qur’an, because al-Qur’an is a way of life for Muslims, no exception blind people. Limitations of learning device of al-Qur’an for the blind becomes an obstacle for the blind to learn Qur'an. This research describes the design of electronic learning device of Iqra Braille for blind people. This system consists of a computer that serves as an interface to manage Iqra braille to be read by the blind people, the mikrokontroler ATMega328P-PU which serves as a data processor of a computing device that can be translated in the braille code, and Braille Display devices which serves to show Braille codes from the data Iqra. Communication between computer and mikrokontroler used Bluetooth media. The results show that the system that has been made to run well. Braille Iqra data which entered by teachers can be displayed on a Braille Display.